Light in the Dark: Thick and Thin Development during the Rana Period in Nepal - Nepal, Ratna Mani (International Journal of Social Sciences and Management, 2025)
In Nepalese political history, the Rana period (1846-1950) is characterized as a ''dark age'' representing the state of skimpy social, economic, and political changes. This article examines the period through modern development perspectives and explores if the politically dark period endured developmental lights. This objective is based on the assumption that development is a necessary as well as sufficient condition of any society in any historical context and, therefore, embedded in its social, economic, and political processes. This article applies a historical and analytical-interpretative approach to examine archival records obtained from various sources, including the TU-Central Library, Gorkhapatra Sansthan, CNAS-TU, and Department of Archeology, Nepal Government, and online databases. Collation of the documentary evidence reveals that the Rana period commenced and endured glimpses of development in perspectives and patterns. The era instituted a foundation of some significant socio-economic development in Nepal. Two concepts can better represent the trends in the period, namely, thick development and thin development. The thick development appears in reform initiatives undertaken by the Rana Regime while grassroots mobilizations represent thin development. This article concludes that in a combination of thick and thin developments, several flashlights qualified the Rana period, the so-called “dark age.” The finding of this article also qualifies the term development. It implies that development transcends history, meaning that development is a historical concept. Any attempt to bracket development in timelines is questionable. It also reveals that development is primarily local, embedded in the specific ecological, social, economic and political contexts of a society. Int. J. Soc. Sc. Manage. Vol. 12, Issue-1: 9-17.